RISIKO PENDIDIKAN IBU TERHADAP KEJADIAN STUNTING PADA ANAK 6-23 BULAN - Atikah Rahayu; Laily Khairiyati (Persagi, 2014)
ABSTRACTMalnutrition constributes to underlying cause of death of Indonesian underfives chilren. One of the consequences of malnutrition in long time period is growth failure that is stunting. Low education of mother is important risk factor for stunting. The aimed of study was to confirm wether maternal education for child stunting in Banjarbaru. Crossectional design was implied to and 51 children aged 6-23 months old were enrolled in study, which run for three months in the year 2013. Maternal education was calculated by year complete of schooling and stunting was by z-score of height for age. Statistical test for data analysis used chi-square test with 95% confidence interval (CI). Result showed that there a significant association (p<0.05) between maternal education and incidence of stunting in children 6-23 months of age. Mother with low education level had 5,1 fold risk to have child stunting. The study confirmed that maternal education had an important risk to child stunting aged 6-23 months old at least in the study site.Keywords: children 6-23 months of age, maternal education, stuntingABSTRAKKekurangan gizi menjadi salah satu penyebab kematian balita di Indonesia. Konsekuensi kurang zat gizi dalam jangka waktu lama adalah gagal tumbuh. Pendidikan ibu yang rendah merupakan factor risiko yang penting pada pertumbuhan anak. Tujuan penelitian adalah mengkaji risiko tingkat pendidikan ibu dengan kejadian stunting pada anak berumur 6-23 bulan. Desain penelitian adalah cross-sectional dengan besar sampel 51 anak berumur 6-23 bulan. Penelitian dilakukan selama 3 bulan di Cempaka, Banjarbaru tahun 2013. Tingkat pendidikan ibu ditentukan dengan pendidikan formal yang telah diselesaikan, stunting ditentukan dengan indikator z-score untuk panjang badan menurut umur. Data dianalisis dengan uji chi-square dengan confidance interval (CI) 95%. Pada penelitian ini ditemukan hubungan yang bermakna (p<0.05) antara pendidikan ibu dengan kejadian stunting pada anak usia 6-23 bulan di Banjar baru. Ibu dengan tingkat pendidikan rendah berisiko 5,1 kali lebih besar memiliki anak stunting. Pendidikan ibu mempunyai peranan penting dalam kejadian stunting anak umur 6-23 bulan di Cempaka, Banjarbaru. [Penel Gizi Makan 2014, 37(2): 129-136]Kata kunci: bawah dua tahun, tingkat pendidikan ibu, stunting